Delivering Together : Using Indonesia's Village Law to Optimize Frontline Service Delivery - World Bank (World Bank, Washington, DC, 2021)
Over the past twenty years, Indonesia has pursued an ambitious policy agenda for decentralization. Indonesia's subnational governments play a key role in providing frontline services. In 2014, Indonesia's Village Law ushered in a new chapter in the country's decentralization agenda. The law establishes a legal and financial foundation for villages to contribute to Indonesia's rural development. In 2020, village transfers accounted for around ten percent of all subnational transfers, playing an important role in Indonesia's Coronavirus (COVID-19) response strategy. Despite these positive results, several frontier issues in the overall decentralization agenda hinder villages' contributing potential to improving frontline service delivery. This report categorizes these structural challenges into four broad categories of regulatory challenges, coordination gaps, limited capacity building systems, and fragmentation in accountability systems. The report aims to show how overcoming these structural challenges can enable the government to institutionalize systems of accountability and participation into its wider service delivery framework.